Analisis Rasio Likuiditas dan Profitabilitas untuk Mengetahui Kinerja Keuangan pada PT Astra Internasional Tbk - Himda Nurika; Sri Hemuningsih (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
To assess the financial level of a company can be done by analyzing the company's financial statements. To find out whether the company's financial condition is in good condition, various analyzes can be carried out, one of which is ratio analysis. The purpose of this study was to determine the financial performance of PT. Astra Internasional Tbk in 2019 – 2021, in terms of financial ratio analysis. The analytical method used is descriptive qualitative analysis, where the data collection method is in the form of a library method, with secondary data types and internal and external data sources. The research shows that the results of financial statement analysis using liquidity ratio measurements, namely the Current Ratio, Quick Ratio with the results of the analysis showing that: the liquidity ratio has increased every year, so that the company's condition is categorized as liquid, while the profitability ratios are Profit Margin, Return on Assets and Return on Equity for profitability ratios show that the company's return on assets has increased so that the company can be said to be more productive than the previous year. Keywords: liquidity ratio, profitability ratio